Research Progress of Soil and Water Conservation in Pisha Stone Area of Yellow River. (September 2020) - Shen, Zhenzhou; Yao, Wenyi; Xiao, Peiqing; Wu, Yan; Song, Jingru; Liu, Jie; Liu, Mingxin; Yang, Jishan; Yang, Haoyu; Duan, Huiling; Li, Li; Dong, Feifei; et al.
Abstract: Ecological degradation and serious soil erosion in the sandstone area of the Yellow River Basin have resulted in a large number of manpower and material resources during the decades-long governance process, and various governance measures have been developed. This article introduces the erosive sandstone area and the existing erosive sandstone erosion control technology, analyzes the methods, materials, and treatment effects of the slope top-slope surface-ditch, and then focuses on the ecology of the Ordos Plateau volcanic sandstone area undertaken by the Yellow River Hydraulic Research Institute. Comprehensively consider the governance technology project, and on the basis of this project, it is envisaged to introduce the concept of buffer zone, in order to provide more research ideas for sandstone governance.